KRİZ HABERCİLİĞİ BAĞLAMINDA TV HABERLERİNİN ANALİZİ: COVID-19 SALGINI ÖRNEĞİ - KÜPE, UĞUR (Fırat Üniveristesi, 2021)
Aralık 2019 yılında Çin'de ortaya çıkan ve kısa sürede tüm dünyayı etkisi altına alan COVID-19 salgını bütün ülkeleri ve insanları, düzen, sağlık, ekonomi vb. alanlarda olumsuz etkilemiştir. Bu salgın günlerce gündemde kalmış ve tüm dünyada kriz durumu yaratmıştır. Ulusal ve uluslararası medyada yer alan salgın haberleri, salgının durumu, seyri ve devletlerin aldıkları önlemler hakkında toplumları bilgilendirme görevi üstlenmiştir. Türkiye'de COVID-19 salgını ile ilgili ilk vaka 11 Mart 2020 tarihinde görülmüştür. İlk vakanın görülmesiyle birlikte Türkiye'deki medya organları salgın ile ilgili toplumu bilgi bombardımanına tutmuş, haber bültenlerinin konusu bir anda COVID-19 salgını olmaya başlamıştır. Bu çalışmada, kriz haberciliği bağlamında COVID-19 salgını haberleri incelenmiştir. COVID-19 salgını haberlerinin incelenmesi için Türkiye'de yayın yapan üç televizyon kanalının (FOX TV, ATV ve CNN Türk) ana haber bültenleri seçilmiştir. Bu çalışmada, kriz haberciliği örneğinde medyanın izleyiciyi karşı sorumluluğunu yerine noktasında nasıl bir yol izlediğine yönelik soruya cevap aranmıştır. Çalışma sonucunda kriz haberciliği bağlamında medyanın izleyiciye karşı sorumluluğunu yerine getirme de farklı yollar kullandığı sonucuna ulaşılmıştır.

COVID-19 pandemic emerging in China in December 2019 and affecting all of the world in a short time has affected negatively all of the countries and people in order, health and economic perspectives. The pandemic has remained in the agenda for days and it has caused the crisis all around the world. Pandemic news appearing on National and International media have taken on a task for informing the societies about the condition and progress of pandemic, and precautions which have been taken by governments. The first case on COVID -19 pandemic in Turkey was appeared on 11th March 2020. With the appearance of the first case, media in Turkey bombarded the society with information on Pandemic, the subject of the main news bulletins turned to be COVID-19 Pandemic in a while. In this study, COVID-19 pandemic news have been researched in the context of crisis reporting. For this research, main news bulletins of three TV channels broadcasting in Turkey ( FOX TV, ATV, CNN Türk) were selected. In this study, an answer was sougt fort he question of what a way the media is followingto fulfill its responsibility against the audience in the case of crisis reporting. As a result of the study it was concluded that the media uses different ways to fulfill its responsibility against audience in the context of crisis reporting.
Analysis of TV news in the context of crisis reporting: A case of COVID-19
Keywords: Gazetecilik; Radyo-Televizyon; İletişim Bilimleri